The Effect of Workplace Raids on Academic Performance: Evidence from Texas - Sofia Avila (Sociological Science, 2024)
Workplace raids are visible and disruptive immigration enforcement operations that can result in the detention of hundreds of immigrants at one time. Despite concerns about the impact of raids on children's well-being, there is limited research on how these tactics affect their academic performance. Using school-level testing data from 2015 to 2019, I compare changes in the performance of Hispanic students in schools close to a workplace raid to white students in the same schools and Hispanic students at control schools. I find exposure to a raid lowered the scores and passing rates of Hispanic students in standardized tests taken 40 days after the operation. I further find that students in schools closer to the raid experienced more pronounced drops in performance, but I do not detect strong evidence that performance decreases were caused by interruptions to schooling. These findings provide new evidence on the spillover effects of workplace raids, underscoring the potential role of immigration enforcement in generating disparities in Hispanic children's educational outcomes.